Debt Sustainability in Low-Income Countries : Further Considerations on an Operational Framework and Policy Implications. (Policy Papers; Policy Paper ;, 2004)
This paper seeks to address queries on several operational issues: (i) the robustness of the indicative thresholds; (ii) modalities for implementing DSAs; and (iii) operational implications for the Fund, Bank, and other international financial institutions and creditors.